Epidemiological characteristics, treatment, and outcomes of 586 cases of intussusception: a 4-year retrospective study in China - Zhang, Lianzhi; Chen, Xiaotong; Huang, Yajun; Wang, Guimei; Zhang, Zhongxi; Song, Zai (Frontiers in Pediatrics, 2024)
Objective: To retrospectively analyze the epidemiological and clinical characteristics of acute intussusception in a tertiary-care pediatric hospital in China over a four-year period, and to evaluate the effectiveness and recurrence of fluoroscopy-guided pneumatic reduction (FGPR) and ultrasound-guided hydrostatic reduction (UGHR). Methods: This retrospective study was conducted from January 2019 to December 2022 among children admitted and managed for acute intussusception in a tertiary-care pediatric hospital in China. The epidemiology, clinical features, and therapeutic effects were analyzed using IBM SPSS Statistics 20.0. Results: The children comprised 401 boys (68.43%) and 185 girls (31.57%) aged 2 months to 12 years. The most common symptoms were abdominal pain (or paroxysmal crying) (95.73%), vomiting (45.39%), and bloody stool (7.34%). Symptoms of vomiting and bloody stool became atypical with increasing age (P<0.001). The total success cases of reduction accounted for 563 cases (96.08%), and the recurrent cases accounted for 71 cases (12.12%). There was no significant difference in success rates or recurrence rates between FGPR and UGHR (P > 0.05). Abdominal pain was independent protective factor for successful enema (P<0.01, OR=72.46) while bloody stool (P<0.01, OR=0.06) and older age were independent risk factors (P<0.001, OR=0.51). Of the 71 recurrent intussusception cases, 29 patients were successfully reduced by enema, and the other 23 cases required surgical reduction. Twelve of the surgical cases were secondary intussusception, including 3 cases of Meckel's diverticulum, 5 cases of polyps, and 4 cases of non-Hodgkin lymphoma. Conclusion: The epidemiological characteristics of children with intussusception in Xiamen showed peculiarity with a higher male-to-female ratio, older age at diagnosis, and no significant seasonality. Both FGPR and UGHR were effective and safe for intussusception, and surgical reduction was essential for patients failed for enema reduction.